Nomadic Models of Postmodern Aesthetics: Soteriological Choice of the Teacher - Kondratska, Ludmyla; Romanovska, Liudmila; Kravchyna, Tetiana; Kozachenko, Svitlana; Novak, Mykola (Journal of Education Culture and Society, 2023)
Aim. The aim of the article is to define the concept of aesthetic competence of the nomad teacher of postmodern era based on a comparative analysis of two aesthetic models (metis paraesthetics and soteriological aesthetics). Methods. The subject of study is anthropotemporal methodology of acquiring aesthetic competence as an act of spiritual transformation (approaches, paradigm, priorities, criteria of effectiveness). The analysis of the stages of nomad’s dianoic choice in the process of understanding beauty as a boon was carried out using the method of epistemological design, according to which emotions function cognitively in aesthetic experience. The technology of spiritual self-coaching was chosen to activate all the structural components of aesthetic competence – the intention to correct aesthetic apperception and the competencies of emotional-reflective, value-semantic, aesthetic and worldview revaluation. Results. The implementation of the chosen technology opened up the possibility of reorientation for the nomad teacher: from the drive of the performer-trickster to a humble and grateful anticipation of the beauty as transcendent – to overcoming the power of inertia of previous dependence, responses to the calls of a pure (still “adventurous”) mind. A cluster analysis of the results of the completed tasks was carried out for the regression description of the efficiency of the technology. Conclusion. The soteriological concept of the aesthetic competence of the nomad teacher focuses attention on the essential coexistence of the teacher with students throughout the entire process of his self-determination. The practical experience of its implementation can make a positive contribution to reforming postmodern aesthetic education.